The blood of government : race, empire, the United States, & the Philippines - Kramer, Paul A. (Paul Alexander), 1968- (University of North Carolina Press, 2006)
In 1899 the United States launched a brutal war of imperial conquest against the Philippine Republic. US imperialists justified their colonial empire by crafting novel racial ideologies. This book reveals how racial politics served US empire, and how empire-building in turn transformed ideas of race and nation in both the US and the Philippines.